2007
DOI: 10.1080/14992020601083313
|View full text |Cite
|
Sign up to set email alerts
|

Real-ear measurement verification for open, non-occluding hearing instruments

Abstract: Real-ear measurements using the modified pressure method with concurrent (real-time) equalization can be inaccurate, when amplified sound leaks out of the ear canal and reaches the reference microphone. In such situations the reference microphone will detect an increased sound level and reduce the output of the loudspeaker to maintain the desired level. The risk of having errors due to leaks increases if digital feedback suppression (DFS) is used, thus achieving higher feedback-free gain levels. The following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
1
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 5 publications
0
19
1
2
Order By: Relevance
“…Uma característica importante das medidas com microfone sonda é sua confiabilidade, sendo relatada variabilidade teste-reteste menores que 6 dB. As principais fontes de variabilidade são o posicionamento do tubo sonda e quebra da vedação acústica ocasionada pela presença do mesmo no conduto auditivo 4 ; a distância e o ângulo de posicionamento do alto falante 5 , o posicionamento do microfone de referência 6 , o método de equalização do campo sonoro 7 , a acústica ambiental e a presença de cerume no conduto auditivo 8 e condições da orelha média 9 . No Brasil existe desigualdade de acesso à educação profissional continuada, gerando diferenças importantes na qualificação profissional de uma região para outra e, por consequência, tornando problemático o acesso a serviços de qualidade.…”
Section: Descritoresunclassified
See 1 more Smart Citation
“…Uma característica importante das medidas com microfone sonda é sua confiabilidade, sendo relatada variabilidade teste-reteste menores que 6 dB. As principais fontes de variabilidade são o posicionamento do tubo sonda e quebra da vedação acústica ocasionada pela presença do mesmo no conduto auditivo 4 ; a distância e o ângulo de posicionamento do alto falante 5 , o posicionamento do microfone de referência 6 , o método de equalização do campo sonoro 7 , a acústica ambiental e a presença de cerume no conduto auditivo 8 e condições da orelha média 9 . No Brasil existe desigualdade de acesso à educação profissional continuada, gerando diferenças importantes na qualificação profissional de uma região para outra e, por consequência, tornando problemático o acesso a serviços de qualidade.…”
Section: Descritoresunclassified
“…Antes do posicionamento do paciente no ambiente de teste, foi realizada a calibração do tubo sonda de acordo com as instruções do manual do equipamento. O método de equalização concorrente foi empregado -ou seja, um microfone de referência posicionado na orelha testada monitorava o sinal que atingia o ouvido do participante e realizava, automaticamente, os ajustes dos níveis de pressão sonora (NPS) no alto falante que fossem necessá-rios para atingir o NPS desejado 7 . A inspeção otológica clínica foi realizada a fim de verificar as condições da orelha externa antes do início das mensurações.…”
Section: Métodounclassified
“…This method reduces the confounding effect of movements of the patient ' s head or any other changes in the sound fi eld between measurements, for example caused by movement of the person performing the test. Lantz et al (2007) reported that the MPCE method is not appropriate for open-fi t hearing aids and that the use of this method may result in underestimation of the REIG. In open fi ttings, a traditional ear mould is not used; instead the sound is delivered to the ear canal via a thin tube or a receiver in aid can leak out of the ear canal and get picked up by the control microphone when measuring the REIG.…”
mentioning
confidence: 96%
“…In open fi ttings, a traditional ear mould is not used; instead the sound is delivered to the ear canal via a thin tube or a receiver in aid can leak out of the ear canal and get picked up by the control microphone when measuring the REIG. This infl uences the output of the loudspeaker and accordingly alters the measured REIG (Larsby & Arlinger, 1988;Hawkins & Mueller, 1992;Lantz et al, 2007). Usually the sound leaking from the ear canal increases the sound level at the control microphone, leading to a reduction in the sound generated by the loudspeaker.…”
mentioning
confidence: 96%
See 1 more Smart Citation